Protests and the Chinese President - an Index of Freedom - Bisley, Sebastian (Victoria University of Wellington Law Review, 2001)
In 1999, the police disrupted several protests aimed at Jiang Zemin, President of the Peoples’ Republic of China, during the APEC Leaders Summit held in New Zealand. In this article, the author considers whether the protesters’ rights under the New Zealand Bill of Rights Act 1990 were infringed by police actions. In doing so, the author traverses relevant international and domestic jurisprudence on freedom of speech, movement and association, including the recent decision of the High Court in Police v Beggs. After concluding that the rights of the protesters were prima facie infringed, the author goes on to consider whether the infringements were justified in a free and democratic society in terms of section 5 of the Bill of Rights Act.